1991
DOI: 10.1021/j100174a014
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of the transition state: hydrogen abstraction reactions of fluorine

Abstract: The reactions F + CH3OH -HF + CH30, F + C2H5OH -HF + C2H50, and F + OH -HF + 0(3P,'D) are studied by photoelectron spectroscopy of the negative ions CH3OHF~, C2H5OHP, and OHP. In each case, photodetachment accesses the transition-state region for direct hydrogen abstraction. The photoelectron spectra exhibit resolved vibrational structure which is sensitive to details of the potential surface in the transition-state region. To aid in the interpretation of the spectra, ab initio equilibrium structures, harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
123
0
7

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(141 citation statements)
references
References 4 publications
(8 reference statements)
11
123
0
7
Order By: Relevance
“…2 and 3 have peaks at 0" and 180" in center-of-mass coordinates, showing clear symmetry about 90". Flux distributions with this symmetry are generally diagnostic of the decay of a transient complex living at least several rotational periods (25,26), supporting calculations that predict the existence of an 0-.HF complex stable relative to 0-+ HF by 187 kJ mol-I (22). In the decay of such a transient complex, the products "forget" the direction of initial reagent approach and the energy distributions are independent of scattering angle.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2 and 3 have peaks at 0" and 180" in center-of-mass coordinates, showing clear symmetry about 90". Flux distributions with this symmetry are generally diagnostic of the decay of a transient complex living at least several rotational periods (25,26), supporting calculations that predict the existence of an 0-.HF complex stable relative to 0-+ HF by 187 kJ mol-I (22). In the decay of such a transient complex, the products "forget" the direction of initial reagent approach and the energy distributions are independent of scattering angle.…”
Section: Discussionmentioning
confidence: 53%
“…Those studies showed that, relative to the thermal energy reference data, incremental translation appears to be partitioned preferentially into product vibration. Knutsen et al have interpreted these observations as a consequence of the attractive well on the potential surface, estimated from ab initio calculations to be 187 kJ mol-' relative to the reagents (22). The drift tube ex~eriments showed that the fraction of the total available energy appearing in product vibration increases linearly with increasing translation up to 15 kJ mol-I, consistent with mixed energy release on the Heavy + Light-Heavy potential energy surface.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, global potential energy surfaces for several electronic states of OHF have been reported. Gómez-Carrasco et al 5 performed high-level MRCI electronic structure calculations for 8069 energy points to calibrate the fitted potential energy surface (PES) of the ground adiabatic 1 3 A triplet electronic state. Quasi-classical trajectory (QCT) and wave packet studies [5][6][7] of F( 2 P) + OH( 2 ) → O( 3 P) + HF( 1 + ) reaction have been performed on this high-quality triplet PES and a subsequent improved version.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the reverse reaction, H( 2 S) + FO( 2 ) → OH( 2 ) + F( 2 P) has been subject to many studies. Gogtas 9 has carried out the quantum real wave packet calculations of the reverse reaction on the ground 3 A potential energy surface. The same reaction has been studied by Zhao et al 10 by using QCT method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation